Isolated Ventricular Noncompaction Cardiomyopathy Presenting as Recurrent Syncope - Sukhdeep Bhogal; Vatsal Ladia; Puja Sitwala; Kais AlBalbissi; Timir Paul (Case Reports in Medicine)
Isolated ventricular noncompaction (IVNC) occurs because of interruption of trabecular morphogenesis in the myocardium leading to ventricular noncompaction. Patients present with heart failure or with systemic complications secondary to thromboembolism or arrhythmias. High index of suspicion is necessary for early diagnosis. We present a case of 48-year-old male with unexplained recurrent syncope who was eventually diagnosed with IVNC.